Implementation of Artificial Intelligence in Strategic Management Decision Making in the Banking Industry - Izzudin, Dani (Maliki Interdisciplinary Journal, 2024)
This article discusses the application of Artificial Intelligence (AI) in strategic management decision-making in the banking industry. With the increasing volume of data generated, banks are required to utilize AI technology to improve efficiency and effectiveness in the decision-making process. Through sophisticated data analysis, AI helps banks understand customer behavior and preferences, predict future needs, and optimize product and service offerings. Despite its many benefits, AI implementation also faces challenges, especially related to data privacy and security. Therefore, banks need to develop transparent privacy policies, implement encryption technology, and conduct employee training to ensure effective data protection. This study uses a literature study method to explore various aspects of the use of AI in banking and the challenges faced. The results show that with the right strategy, banks can improve customer experience and maintain public trust while maximizing the potential of AI.